Modeling Musical Capabilities – Guitar Playing - Stanescu, Dan Florin (European Scientific Journal, ESJ, 2016)
While it is possible for one to detect a person’s dexterity upon an instrument visually, auditorily and sometimes even kinaesthetically, it is the hypothesis here that there are other sets of skills which are just as important to musical capability as the manual technique applied when playing the instrument. Modeling is a process whereby an observer gathers information about the activity of a system with the aim of constructing a generalised description (a model) of how that system works. The purpose of this study is to identify strategies and patterns in how musicians organized their experience of the world around them and then acted in that world so that we may gain some new insights on how they operate. In order to get relevant data, direct observation and interview were employed. For this purpose three exemplar were selected. With each of them an in-depth interview was conducted (videotaped). All the components of the schema were elicited, using an interview schedule (Darlington & Scott, 2002, 141), which followed Dilts logical level model (Dilts, 1998). At the end of the interview each exemplar was asked to perform a piece of music for a live observation of exemplar achieving their results (Frost, 2011).